2013
DOI: 10.1080/02640414.2012.738924
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rest intervals on jumping performance: A meta-analysis on post-activation potentiation studies

Abstract: The purpose of this meta-analytic review was to examine the extent and quality of research on the post-activation potentiation acute effect of rest interval manipulation on jumping performance. This manuscript adopted the recommendations from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement. Criteria eligibility included crossover, randomised, non-randomised and counterbalanced studies that observed the voluntary muscle action-induced post-activation potentiation on jumping perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 30 publications
9
65
0
11
Order By: Relevance
“…The dependent variables were the maximal CMJ height, number of kicks, and maximal impact of kicks. These variables were chosen because they represent the athlete's muscular power performance and were used in other studies that investigated the PAP (11,14,27). A 90-minute rest interval was given between 2 experimental conditions conducted in same day and 48 hours between days ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variables were the maximal CMJ height, number of kicks, and maximal impact of kicks. These variables were chosen because they represent the athlete's muscular power performance and were used in other studies that investigated the PAP (11,14,27). A 90-minute rest interval was given between 2 experimental conditions conducted in same day and 48 hours between days ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have investigated the effect of different rest intervals by using independent experimental sessions (11,23,27), i.e., likely an additive effect took place in many studies. The exercises most used during conditioning activities are squats (moderate and heavy load), jumps, and the complex method (high-intensity exercise followed by plyometric exercises) (11,27).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the ability of a muscle group to produce force can be influenced by the contractile history of that given muscle group (25), modification of the warm-up to include conditioning contractions has been suggested (26). Post-activation potentiation (PAP), an acute and temporary enhancement of muscle performance as a result of its contractile history (34), elicits transient improvements in performance that exceed those attributable to warm-up alone (5,7,8,18,19,(25)(26)(27)36,38).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other practical strategies employing different volume parameters, contractions, and rest times should be investigated. Currently, a 7-12 minute recovery interval has been suggested to optimally enhance the potentiation response to exercise (Wilson et al, 2013, Gouvêa et al, 2013). In the current study, a 1-minute rest was allotted between the pre-conditioning contraction and the performance measure.…”
Section: Effect Of Hip Abduction Maximal Voluntary Isometric Contractmentioning
confidence: 99%
“…It is plausible that a greater rest period may be warranted to accommodate the fatigue theory associated with the potentiating mechanisms. Additionally, it has been suggested that the potentiation effect is more sensitive in experienced individuals (Wilson et al, 2013, Gouvêa et al, 2013, therefore MVIC protocols may be more applicable in elite, competitive strength/power athletes (e.g. powerlifters).…”
Section: Effect Of Hip Abduction Maximal Voluntary Isometric Contractmentioning
confidence: 99%